Impact of nurturing care educational videos focusing on children with nutritional problems aged 6-23 months on mothers' knowledge and child growth - Haryanti, Fitri; Lusmilasari, Lely; Hartini, Sri; Sandhi, Ayyu; Parmawati, Ika; Akhmadi, Akhmadi; Hasanah, Nisa Nur; Andarwati, Fitriana; Risnawati, Hani; Pratiwi, Alissa Nur; Kusumawati, Ananda Sekar; Cahyani, Redyta Dwi (MEDISAINS, 2024)
Background: The first 1,000 days are crucial for a child's development. Indonesia has limited research on responsive caregiving and early learning opportunities, especially for children with nutritional challenges. While studies have addressed general child nutrition, few have explored comprehensive nurturing care interventions. This gap underscores the need for further research. Educational videos, particularly animated ones, effectively capture attention and improve understanding, making them valuable for enhancing maternal knowledge and child growth.Purpose: This study aimed to assess the impact of nurturing care educational videos on mothers' knowledge and child growth in children aged 6-23 months with nutritional challenges.Methods: A quasi-experimental design with non-equivalent and untreated control groups was employed. Seventy-three mothers and their children aged 6-23 months, facing nutritional challenges, were recruited through consecutive sampling. The intervention group received nurturing care educational videos. Statistical analyses included dependent t-tests, independent t-tests, and repeated measures ANOVA.Results: The intervention group showed significant improvements in nurturing care knowledge (p = 0.012), responsive caregiving (p = 0.018), and safety and security (p = 0.006). A significant difference in safety and security was observed between groups at posttest 1 (p = 0.020). Both groups exhibited significant increases in children's body weight and height: the intervention group (body weight, p = 0.005; body height, p < 0.001) and the control group (body weight, p < 0.001; body height, p < 0.001).Conclusion: Nurturing care educational videos had a significant positive impact on enhancing mothers' knowledge and promoting child growth. Notable improvements were observed in nurturing care knowledge, responsive caregiving practices, and safety and security measures among caregivers exposed to the intervention.